SOCIO-CULTURAL AND PHILOSOPHICAL-LEGAL DIMENSIONS OF THE GENDER IDENTITY PROBLEM - V. S. Blikhar; I. M. Zharovska; I. O. Lychenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Based on the comparative analysis of the European and post-Soviet countries, the purpose of the article is to study one of the manifestations of gender discrimination, namely the problem of gender equality in the sphere of labor. It involves the consistent solution to the following tasks: a) to emphasize the basic principles of gender international and legal policy; b) to reflect the praxeological dimension of providing the equal social and economic opportunities for men and women at current level; c) to emphasize the key criterion for ensuring the equality in socio-cultural sphere – equality in political life; d) to study the educational level of women and the possibility of self-realization in employment equal to men. Theoretical basis. The authors proceed from the standpoint that gender equality at the present stage has become a priority of legal policy and an important principle of the state (legal and democratic) of pro-European orientation. It is characterized in the legal plane, first of all, by the equality of the social roles of men and women, and the overcoming of the gender hierarchy of social ties, in which men are perceived as higher beings by their mental and physical abilities, and their activities are more significant and of priority in comparison with the activities of women. Originality. The authors have substantiated that in many economically developed countries the problem of providing a gender is still relevant, but most of the crisis problems in this area have found their legal regulation. The motivated position of the authors is that the level of education and professionalism of women cannot serve a reason for discrimination against women, which now exists in the economic and political sphere in the post-Soviet space. Conclusions. Gender stereotypes remain the priority in woman’s keeping family household, which creates significant inequalities of women and men at the labor market. Specialized regulatory acts in the field of gender declare the equality of men and women, while labor law defines a number of norms and guarantees that complicate the employment of women. In order to improve the situation we propose to implement a number of measures, such as, creation and financial support of the programs at the state level for supporting maternity, family and childhood; examination of all normative acts and concerning the issue of gender asymmetry, and especially the norms of labor law; introduction of state monitoring of employment and income of persons as to the complying with the principle of gender equality; introduction of quotas for women’s participation in political activities, in the work of the government and parliament, etc.